A fertiliser composition. - Ahmed, Osumanu Haruna; Shamsudin, Rosliza; Kasim, Susilawati; Nik Ab. Majid, Nik Muhamad (2009)

(untitled)
The present invention discloses a urea-based fertiliser composition that is capable of reducing the loss of ammonia from urea when applied on soil. Accordingly, the present invention provides a fertiliser composition suitable for use as a plant nutrient, the composition comprising urea and an organic acid or mixtures thereof. The organic acid comprises fulvic acid or a mixture of fulvic acid and humic acid extracted from palm oil mill effluent sludge, which is capable of controlling the dissolution and hydrolysis of urea, thereby reducing the loss of ammonia from the composition.